Synthesis and characterization of push–pull bithienylpyrrole NLOphores with enhanced hyperpolarizabilities - Castro, Maria Cidália Rodrigues (2016)
Novel pushepull second harmonic generation (SHG) chromophores 3-6 were synthesized in order to study how their optical properties are affected by an increase in the size of the p-bridge and also by connecting different electron accepting moieties (dicyanovinyl- and tricyanovinyl) to the (bi)thienylpyrrole system at position 5 of the pyrrole ring or at position 5 of the thiophene heterocycle. The precursor aldehydes were prepared through two different synthetic methodologies: Suzuki coupling (5ab) or Suzuki coupling followed by Vilsmeier formylation (2a-b). The final donor-acceptor systems 4-6 were prepared by tricyanovinylation reaction of precursors 1a-b or by Knoevenagel reaction of the precursor aldehydes 2b or 5b with malononitrile. Hyper-Rayleigh scattering in dioxane solutions using a fundamental wavelength of 1064 nm was employed to evaluate their second-order nonlinear optical properties. The experimental results showed that the optical properties are influenced by the electronacceptor strength of the groups, the length of the p-spacer/donor group as well as by the relative position of the pyrrole and thiophene heterocycles to the acceptor groups. The dicyanovinyl derivative 6b, which embodies the longer p-conjugated bridge functionalized in the thiophene ring, exhibited the largest first hyperpolarizability (b= 10,900x10 -30 esu, using the T convention) thus indicating its potential application as a SHG chromophore. As far as we are aware, this represents the largest hyperpolarizability reported to date for a bithienylpyrrole derivative.